The Effect of Interpersonal Communication Skills, Social Support, and Coping Strategy on Resilience in Master of Nursing Students Who Work on Thesis - Munawaroh, Lailiyatul; Hayati, Yati Sri; Yuliatun, Laily (Poltekkes Kemenkes Palu, 2024)
The majority of Master of Nursing Students are experiencing moderate to high levels of stress. Especially while working on their thesis. High-stress levels in nursing students can make them vulnerable to mental health disorders. One of the interventions to solve this problem is by building their resilience. Several previous studies related to resilience in nursing students focus more on undergraduate students. This study aims to analyze factors related to resilience in a master of nursing students in one of the state universities in East Java who are working on a thesis and see the fit of the resilience model. This study used a cross-sectional design with a total sampling technique. The minimum sample size is 10x the number of exogenous variables studied. There are 6 exogenous variables in this study so the minimum sample size is 60 respondents. The sample in this study amounted to 63 respondents. Univariate analysis in this study was carried out by analyzing numerical data using mean, median, and standard deviation values. Meanwhile, for categorical data, proportion analysis is used. Multivariate analysis was carried out using Partial Least Square (PLS) using SmartPLS 4. The result of this study shows p-values for X3 and Y, X5 and Y, X6 and Y, X1 and X6, X4 and X6 are below 0,05. So it can be concluded that interpersonal communication skills, social support, and coping strategies are positively related to resilience. Spirituality and physical health were not related to resilience but were positively related to coping strategies. Meanwhile, emotional intelligence is not related to either of them. The resilience model is a good fit. Further research by improving the research design is needed to support the results of this study.